Вы находитесь на странице: 1из 21

1

1. . .
-
-
- .
:
1 : ={: ()} - ...
A={-()}
() - = ,
. .
2 : :
AB = {c: cA cB}, AB = {c: cA cB}, A\ B = {c: cA B}
U - ()
UA; U \ A = A = cA (A - A)
:
1. A(BC)=(AB) C - ; AB=BA - ; A=A; AU=U
2. A (BC)=(AB) (AC) & A (BC)=(AB) (AC) - ; =
A =A - (AB)=AB; (AB)=AB; AA=
: -.
"=>" c(AB) => cAB => cA & cB => c A & cB => cAB
"<=" cAB => cA & cB => cA & cB => cAB => c(AB)
:
f:A ( f B)
aA; b => b - f; a - b f
, -
(Dom f=), B (Im f B)
: 1) 2) Dom 3) Im
f f(x)=f(x) => x=x( )
f Im f =B( )
+, (
- ), - .
- (N)
: Q .
Z
: Q= , n N
n =1 n
1: nN Z/n - .
N Z/n:
100/n 5-2/n
2+1/n 6+3/n
3-1/n 7-3/n
4+2/n ...
2: ( ) .
1={11, 12, 13,...}
2={21, 22, 23,...}
3={31, 32, 33,...}
...
(11 - 1; 21 - 2; 12 - 3; 31 - 4; 22 - 5...)
,
- .
: (-1,1) R ( )
1 2 :
2. . Q R.
- [a0],1 a2 3... 0Z 1,2,3,... {0,1,...,9}
:
[],1 2 3... (0) = + 1/10 + 2/100 + ... +/10k = [],1 2 3... (9), =-1
=[],1 2 3......
=[],1 2 3......

2
- = [],1 2 3...
- = [],1 2 3... + 1/10k
+1 > ( - )
+1 k (k - ), .. =[],1 2 3... + 1/10
+1 = [],1 2 3... +1 + 1/10+1
- +1 = 1/10 - +1 + 1/10+1 0
10 - +1 - 1 / 10+1 0
9 +1
: 1) > <=> : >
2) = <=> > & >
, [1],(0)=[0],(9)
: 1) , <, >, =
2) > & >z => >z
3) >
- (2): >
>z
>
m>zm
n=max{k;m}
n>n
n m>zmzn
n>n => n>zn
: R ,R : <<, R
: Q R.
: > >
/ 2 + / 2 > / 2 + / 2 > / 2 + / 2 >
: > / 2 + / 2 > , ( / 2 + / 2)Q
3. .
: R .
:
11=[1], 11 12 13... |
22=[2], 21 22 23... |
33=[3], 31 32 33... |
...
| (*)
=[ ], 1 2 3... |
...
|
:
=[], 1 2 3...
[][1]
=> 1
1 {9;21} => 2
2 {9;32} => 3
...
{9;+1} =>
- (*)
5. R
1) 0R; 2) aA, b: <b; 3) B=R, ! R: aA, b: b
: 1) Q I (
Q R)
2) ( ),
( )
:
aA, b: <b => A => SupA=m => b: bm => B
=> InfB=n, mn
, m = n:
m<n, Q R , Q: m<c<n => c & c 3 , mn
, m=n m=n c, b
, ( ):

3
,> (<), c=n=InfB=m=SupA=> -. > (<) b(a),
b<c (a>c)- aA, b: b
8. ( )
n0: n>n0 xNyNzN Lim xN=x, Lim zN=z, x=z, Lim yN=y => x=y=z.
: n>n0 xNyNzN
>0, n: n>n xN(-,+) & n: n>n zN(-,+) =>
n>max{n0,n,n} yN(x-E,x+E)
4. .
: R mR, m - () , m (m).
: A (), m, ,
m (m).
: SupA=m, 1) m - A
2) m: m<m => m A
InfA = n, 1) n - A
2) n: n>n => n A
: SupA=m , : 1) aA am
2) >0 aA, , a>a-
InfA = n , : 1) 1) aA an
2) >0 aA, , aE<a+
: , R, ,
.
:
m .
[m]=max{[a]:aA} [[m],[m]+1]A=>[m]+1 - A
[[m],[m]+1] - 10
m1=max[10*{a-[m]:aA}]
m2=max[100*{a-[m],m1:aA}]
...
m=max[10K*{a-[m],m1...mK-1:aA}]
[[m],m1...mK, [m],m1...mK + 1/10K]A=>[m],m1...mK + 1/10K - A
, m=[m],m1...mK - :
: [mK,mK)A0; : <mK
( ):
, >mK => : K>mK => K>mK - => am
:
l<m, : mK>lK, [mK,mK) A0 => [mK,mK) => >l =>l -
.
: , R, ,
.
B{-: }, => -SupB=InfA
6. . .
: N ()
(>0 n0: n>n0 |N|<)
: () .
: Lim aN=Lim bN=0, cN=aN+bN, dN=aN-bN. 0 ( /2)
aN, .. n: n>n: |aN|</2. n: n>n: |bN|</2.
n>max{n,n} |a N|</2 & |bN|</2 => n> max{n,n} :
|cN|=|aN+bN||aN|+|b N|<E/2 + E/2 = E => |dN|=|aN-bN| |aN|+|bN|<E/2 + E/2 = E
: - .
: aN - -, bN - - zN=aN*bN.
.. bN - -, : |bN|0

4
.. aN - -, - 0 ( /)
- aN, .. n0: n>n0 |aN|</. n>n0: |zN|=|aN*bN|=|aN|*|b N|</ *
=
: - - -
: aN - . n: n>n |b N|aN => bN -
: aN - => n: n>n: |aN|<. n>=max{n,n} |bN||aN|<
: N () >0 n0: n>n0 |
N|>)
: aN - , 1/aN - , .
:
"=>" aN-=> - 0 ( 1/)
-, .. n0: n>n0 |aN|<1/E =>1/|aN|>.
"<=" 1/|aN| - => >0 n0: n>n0 1/|aN|>1/ => |aN|<
: aN - . n: n>n bN|aN| => bN - .
: aN - => n: n>n |aN|>. n>max{n,n} bN|aN|>
7.
: aN aN-a
( )
: .. Lim aN=a, |aN-a|<. N=aN-a. |N|=|aN-a|<
: N=aN-a, .. N - => |N|. |N|=|aN-a|<
: Lim xN=x, Lim yN=y, :
1. Lim (xN+yN) Lim (xN+yN)=+
2. Lim (xN*yN) Lim (xN*yN)=*
3. n yN0 & y0 => Lim (xN/yN) Lim(xN/yN)=/
:
xN=+N, N - ; yN=+N, N -
1) (xN+yN)-(+)=N+N ( : N+N - => (xN+yn)-(+)-,
)
2) xN*yN - * = *N+*N+N*N ( - * - . : xN*yN - * - , -)
3) xN/yN - / = (*N-*N) / (*(+N))= (*N-*N) * 1/ * 1/N
: n - 0 -, 1/N
: Lim N=y => n0: n>n0 |n-|</2 (=y/2),
: -/2<N</2+, : |N|N>/2.|N|>/2=>1/|N|<2/
=> n: 1/|N|max{2/, 1/1, 1/2,...1/no}
: N , yN n0: n>n0 NN,
( ): >. . E>0 ( <(-)/2): n:
n>n |xN-x|<E n: n>n |yN-y|<E. n>max{n,n} - xN
- , - N - ,
(-,+)(-,+)=. . , >, n>max{n,n}: N>N => .

5. .
: .
, ,
f f: (f()| ).
: - - - N, - R
f:NR. - (.) nN N.
:
1) :

5
2) : () :
. (
) ,
. : 1=; N+1=N +
3) : : : N = n-

: N, >0 n0: n>n0


|N-a|<. Lim aN=a.
, -,
, , ( ).
, (,+), - , N
, , -
N.
: - N
.
: .
( ):
N , . ,
- .
|-|/2.
=>
- , - .
: .
:
N . - , ,
, ,
.
: 1) (n=(-1)N, )
2) N,
.
:
: Lim xN=x, Lim yN=y, n0: n>n0 NyN, xy
( ):
> => n0: n>n0 |N-|<E( <|-|/2): & n0: n>n0 |yN-y|
<E. n>max{n0, n0}: |N-|<|-|/2 & |N-|<|-|/2, .. 2 (-,+) & (,+)], (-,+)(-,+)=. n>max{n0, n0} N(-,+) & N(-,+)
, > : n>max{n0, n0} N>yN - .
: n0: n>n0 aNbNcN Lim aN=a, Lim cN=c, a=c, Lim bN=b => a=b=c.
: >0, n: n>n => cN<(a+E) & n: n>n => (aE)<aN. n>max{n0,n,n} (a-E)<aNbNcN<(a+E), .. n>max{n0,n,n}=>bN(a-E,a+E)
9.
: ()
n1>n2 (n1<n2): xN1xN2 (xN1xN2).
: xN1 () xN2, -
()
().
: .
: N . ={xN:
nN}
: SupX=x,
>0 xE: (-)<E => n0 xNo>(-E). : n>n0 xNxNo>(x-E),
xNx=SupX, n>n0 xN(x-E,]<(x-E,x+E)
10.

6
: ,bR <b. 1-5 -
:
1) M R: b (<<b) - ()
2) M R: <b (<b) - ()
3) M R: < & x<b -
4) M R: & b -
5) M R -
: b ( )
( ), b-a
: aN , bN , n aNbN (bN-aN)-, ! :
n c[aN,bN] ( [aN,bN])
:
aNbNb1 aN & aNb1 => Lim aN=a
a1aNbN bN & a1bN => Lim bN=b
aNa bbN aNbN => ab
Lim (bN-aN)=b-a=0( )=>a=b
c=a=b, aNcbN
: aNcbN,
aNcbN=>-bN-c-aN => aN-bNc-cbN-aN => ( ) => Lim(a NbN)Lim(c-c)Lim(bN-aN) => (a-b)Lim(c`-c)(b-a) =>
0lim(c`-c)0 => 0(c`-c)0 => c=c => c - .
: z -
( 1 2 1
2: [a1,b1],[a2,b2],...,[an,bn]...,
, 0 n lim(bN-aN)=0,
aN bN ( ).

11. . -.
: N - kN- - N .
- naN nkN - aKn- . - aN=>- - - -,
.
: Lim N=, Lim Kn=.
: -
n .
: n0: n>n0 |N-|<,
kN n, n>n kN>n0 n |
Kn-|<
-:
.
: N - => n: Nb. [a,b] ,
- N (
-, ). [1,b1] , -.
[1,b1] [2,b2] - N.
- [K,bK]-
- N. -
bK-K = (b-a)/2K, 0 KK+1 & bKbK+1.
! : n NcbN.
:
N1 [1,b1]
N2 [2,b2] n2>n1
...
NK[K,bK] nK>nK-1
Nkb. (Lim aK=LimbK=c )

7
Lim Nk=c - ...
12. .
xN - =>n NNbN
NK, NK- => n Nb =>b
- N
- .
(b) => SupM & InfM
- xN SupMSup{xN}: Lim xN
- xn InfMnf{xN}: lim xN
C .
:
: N (), - NK:
() N.
: =SupM= N
: -1/< ( - Sup), .. => NS
=> >0 ( =1/) s0: s>s0 =>
-1/<NS<+1/
-1/-1/<-1/<NS<+1/<+1/ (..-1/< <=Sup)
-2/<NS<+1/
=1: -2<NS<+1, . s0: s>s0 - NS
s0 N1
k=1: -2/1<N1<+1/1
k=2: -2/2<N2<+1/2 n1<n2
...
k=k: -2/<NK<+1/ nK-1<nK
NK
13. .
: {N} - , >0 n0: n>n0
N |N+-N|<. >0 n0,
-, n0 , .
-: , -
, .
:
: Lim xN=x, >0 n0: n>n0 |N-|</2. n>n0, n>n0 |N-N|=|N-+-N|
<|N-|+|-N|</2+/2<
: N -
1) N : 1=1998 n0: |N-N|<, n>n0, n>n0
n>n0 |N-N0|<1 N0-1998<N< N0+1998 => N -
2) -
- NK. , |NK-|</2
n>n0. ( -) | N-NK|</2 =>
|NK-|</2 => -/2<NK<+/2 => |N-NK|</2 => NK-/2<N<NK+/2 => -<N<+ => |N-|<
14. . .
:
(1 + x ) n = Cn0 + Cn1 x + Cn2 x 2 +...+Cnn 1 x n 1 + Cnn x n n
1
1 2
1
(1 + x ) n +1 = Cn0 + Cn
x + Cn2 x 2 +...+Cnn 1 x n 1 + Cnn x n + x + Cn
x + Cn2 x 3 +...+Cnn 1 x n ...+Cnn x n +1 = Cn0+1 + Cn
+1 x

Cn0 = Cnn = 1
Cn1+1 = Cn1 + Cn0

Cn2+1 = Cn2 + Cn1

( - )

...
Cnk+1 = Cnk + Cnk 1

n!
=0,1,...,n
k !(n k )!
( ):
1) n=0 - (1+)0=1 => Cn0 = 1 (1+)0 = Cn0 = 1
2) n: n+1:
Cnk+1 = Cnk + Cnk 1 =
k
*: Cn =

n!* (n - k + 1)
n!* k
n!
n! * (n + 1)
(n + 1)!
n - k +1 k
+
=
*
+ =
=
x! * (n - k)! * (n - k + 1)
(k - 1)! * x * (n - k + 1)! k! * (n - k + 1)!
1
1 k!* (n - k + 1)! k! * (n - k + 1)!

..

n!
n * (n - 1) * (n - 2)*...*(n - k + 1)
=
k !(n k )!
1 * 2 * 3*...*k

Cnk =

16.
1) Lim

1
np

1
np

, n n ( n )

= 0 (p>0)
1

1
n

< E <=> n p >

2) Lim
xN=

nn

nn

1
1p
<=> n >
E
E

- , n0= 1 p : n>n0 | n p |<E


E

=1

-1

nn

=1+xN
n=(1+xN)n
1
2
2
n-1
n-1
+ xn >
n= 1 + C n * x + C n * x +...+C n * x

n * (n - 1)
* xn2
2

xN2<2/(n-1)
0 < xn <
nn

2
n
(n - 1)

2
(n - 1)

0 => xN0 ( )=>Lim

=Lim (1+xN)=1+0=1

19. (1+1/n)n .
n
1
1
1
1
1

+
+...+
xN= 1 + ; yN= 1 +
; zN=yN +

n
1! 2 !
n!
n * n!
xN : :
x n +1
1
= 1 +

xn
n + 1

n +1

1 +

(n + 2) n +1 * n n +1
(n + 1) 2 n +2

n +1
n 2 + 2n + 1 1

2
n
n + 2n + 1

n +1

n +1
1
=
1
n
(n + 1) 2

xN=(1+1/n)n=1+ n/1!*1/n + n*(n-1)/2!*1/n2 +... < 1 + 1/1! + 1/2!+...+1/n! = yN => yN<zN<3


(1+x)n1+nx, x>-1) ( ):
x=1/n => (1+1/n)n1+n/n=2
: 2 xN<3 => xN - , xN - => xN -
.
17.

1 n
, n ( n )
an a

1) Lim n a =1, a>0


a) a1:
xN= n a xN+1= n+1 a
xN+1=xN * n*(n+1) a

xn
n*(n+1)
=
a * 1 => Lim xN=x
x n+1

n +1

n +1
1
n

xN=xN+1 * n*(n+1) a
xN=xN+1*xN*(n+1)
Lim xN=Lim (xN+1*xN*(n+1)) => x = x*x => x = 1
) 0<a<1 b=1/a xN= n a
Lim

nb

2) Lim
xN=

n
a

=1 b=1/a => n a = 1/ n b => Lim n a = 1/1 = 1


n
an

= 0, a>1

xN+1=

n + 1
a n +1

x n+1 n + 1
=

n
xn
x n+1 n + 1
=

n
xn

xN+1=xN*

n + 1

n + 1

1
= Lim 1+
.. Lim
n

1
n

=Lim 1+

=1

1
1
< 1 => n0: n>n0 xn+1/xn<1 => x=limxn

Lim xN+1 = Lim xN*

n + 1

=> x = x*1/a => x=0

, xN1 => (xN)1:


a) n: xN1 0
(xN) [](xN)<(xN)[]+1 =>
-, Lim (xN)
[]
[]+1
=Lim (xN) =1 ( Lim ) Lim (xN) =1
) n: 0<xN<1 0
yN=1/xN => yn>1 Lim yN=lim1/xN=1/1=1 => ( ()) Lim (yN) =1 => lim 1/(xN) =1 => Lim (xN) =1
() ():
xN1 >0
xN1,xN2,...>1 (1)
xM1,xM2,...<1 (2)
1 (1) (2) =>
xN.
) <0
(xN) =1/(xN) <0 => ->0 => >0 , Lim 1/(xN) = 1 => Lim
(xN) = 1
18. e=...
1
1
1
1
+
+...+
yN= 1 +
; zN=yN +
1!
2!
n!
n * n!
1) yN
2) yN<zN
3) zN-yN0
4) zN
:
1
1
n +1
1
1
zN-zN+1 = yN +
- yN+1 =
+
=
(n + 1) * (n + 1)!
(n + 1)!
n * (n + 1)! (n + 1) * (n + 1)!
n * n!
1
1
1
1

* -1 + 1 + =

(n + 1)!
n n +1
n (n + 1)(n + 1)!

2=y1<yN<zN<z1=3
e = Lim yN = Lim zN - : yN<e<zN = yN + 1/(n*n!)
e - yN 1/(n*n!), e - yN
= /(n*n!), yN e = yN + /(n*n!), (0,1)
e :
( ): e=m/n, mZ, nN

10
m/n = e = yN + /(n*n!)
m*(n-1)!= yN*n! + /n, (m*(n-1)! & yN*n!)Z, (/n)Z =>
20. . .
: f(x) 0 >0 >0: 0<|-0|< & Df => |
f(x)-|<
: f(x) 0 N0,
N0 f(xN)
: :
-: ,
.
1) ()=>()
>0 >0: 0<|-0|< & Df => |f(x)-|< -
N0, N0, .. N0 => n0: n>n0 0<|xN-x0|< (=) => 0<|xN-x0|< => |
f(xN)-|<
2) ()=>() : B ,
:
() => ()
(): >0: >0 x: 0<|x-x0|< => |f(x)-A|E
(): N0, N0: |f(xN)-A|E
N0, N0 => n0: n>n0 0<|xN-x0|< (=) => |f(x N)-|
- f() (,+), N
: limf() N = Limf(1/t) t+0
( ). Lim f() N = Lim f(1/t)
t0 N = lim f(1/t) t0
24. . . .
Lim(0|h|) h0 . ( ) - f(x) . 0
.: (x0-,x0+)\{x0} .. - >0. Lim
f(x) . 0 - <=> c- f(x) . 0 .
: f() - => >0 >0: -<-0< => |f()-|<, ..
, - . x0 f() () (f(),f()+). . (0, x0+) => x . (x0-,x0+) => f() .
(f()-,f()+) => - . . (x 0-,0) => x
. (x0-,x0+) => f() . (f()-,f()+) => -
.
: Lim (0|h|) h0: Lim(0+|h|) = Lim(0-|h|)=
>0 >0: 0<-0< => |f()-|<
>0 >0: -<-0<0 => |f()-|<
>0 0<=min{,}: - <-< => |f()-|<
.1: - f(x) . . 0 0 Lim f()=f(0).
- f(0) . f(x) 0. . - |f()-f(0)|< =0 => .
0 => .:
.2: - f(x) . . 0, >0 >0: - <-< => |f()-f()|<
0 - - :
.3: - f(x) . . 0, - N0, f(xN)f(a)
0 limf()f(0), - f(x) . 0. :
) f() 0
) f() . 0
) f() 0 limf() 0 f()=f()
: 1) . I , - (
, f(0)
2) . II - - .
0 , 0 . . .

11
, 0 -
.
x0 . , x0 . ,
.
() . 0 f(x0), f(x) .
().
f(x) () . 0 -, () -
f(0), - f(x) . 0 (). -
f(x) . 0.
- f(x) . .
.
22. . .
: 0: - f:R g:R (R) , Lim f(x)=F,
Lim g(x)=G,
1) Lim f(x) Lim g(x) = FG
2) Lim f(x)*Lim g(x) = F*G
3) G0 g(x)0 Limf (x) / Lim g(x) = F/G
:
1) >0( /2) >0: -<-0< => |f()-F|< & >0: -<-0< => |g()-G|<
>0 0<=min{,}: -<-0< =>-/2 - /2<f()-F+g()-G</2 + /2 => |(f()+g())(F+G)|<
2) - N0 (N0, xNX), :
n Lim f(xN)=F & Lim g(xN)=G - : n
Lim f(xN)*g(xN)=Lim f(xN)*Lim g(xN)= F*G => 0 Lim
f(x)*Lim g(x)=F*G
3) - N0 (N0, xNX), :
n Lim f(xN)=F & Lim g(xN)=G - :
n Lim f(xN)/g(xN)=Lim f(xN)/Lim g(xN)=F/G => 0 Lim
f(x)/Lim g(x)=F/G, G0 g(x)0.
:
: X: f(x)g(x), 0 A=Lim f(x), B=Lim g(x), AB
( ):
A>B => ( 0<<|A-B|/2): >0: |-0|< => |f(x)-A|<E
& >0: |-0|< => |g()-B|<.
, 0<=min{;}: |-0|< => |f(x)-A|<|A-B|/2 & |g()-B|<|A-B|/2, >
(-,+)(-,+)=,
(0-, 0+) f(x)>g(x) - .
: X: f(x)g(x)h(x) 0 Lim f(x)==Lim h(x), Lim g(x)=
:
>0 >0: |-0|< => A-E<f(x) & >0: |-0|< => h()<A+.
, 0<=min{;}: |-0|< => A-E<f(x) & h(x)<A+E, X: f(x)g(x)h(x)
=> A-E<f(x)g(x)h(x)<A+E => A-E<g(x)<A+E

23. . (Sin x)/x 0.


1) Sin x:
Lim Sin x = Sin x0 ( 0)
|Sin x-Sin x0|=2*|Sin((x-x0)/2)|*|Cos((x+x0)/2)| < 2*|(x-x0)/2|=|x-x0| => -|x-x0|<Sin x-Sin x0<|x-x0|
0 => -|x-x0|0 & |x-x0|0 => ( - ) (Sin x-Sin x0)0
2) Cos x:
Lim Cos x = Cos x0 ( 0)
Cos x = Sin (/2 - x) = Sin y; Cos x0 = Sin (/2 - x0) = Sin y0

12
|Sin y-Sin y0|=2*|Sin((y-y0)/2)|*|Cos((y+y0)/2)| < 2*|(y-y0)/2|=|y-y0| => -|y-y0|<Sin y-Sin y0<|y-y0|
yy0 -|y-yo|0 & |y-yo|0 => (Sin y-Sin y0)0 => : [Sin (/2 - x)Sin(/2 - x0)]0 => (Cos x-Cos x0)0
3) Tg x - - = /2 +2, Z
4) Ctg x - - = , Z
: Lim (Sin x)/x=1 ( 0), 0<x</2
:

- (S=*R 2)
Sinx<x<Tgx, 0<x</2. => Cos x < (Sin x)/x < 1. -
-: Lim Cos xLim (Sin x)/x1 x0, 0<x</2.
os1Lim (Sin x)/x1 => Lim (Sin x)/x =1, 0<x</2
24. .
: ,bR <b. 1-5 -
:
1) M R: b (<<b) - ()
2) M R: <b (<b) - ()
3) M R: < & x<b -
4) M R: & b -
5) M R -
: f(x) [a,b] - f() f(b),
0[a,b]: f(0)=c.
: g()=f()- (g(x) - ). g()*g(b)<0
[a,b] , g((+b)/2)=0, 0=(+b)/2
(g(0)=f(0)-=0 => f(0)=). g(x)
, ,
g(1)*g(b1)<0, g(x) =>
. g(x) ,
g(2)*g(b2)<0...
- - g(x) ,
,
. n- [aN,bN] : g(aN)<0, g(bN)>0,
bN-aN=(b-a)/2n0 n. -
=> x0 [a,b], Lim aN=Lim bN= x0.
, x0- : g(aN)<0, g(bN)>0 => :
Lim g(aN)0, Lim g(bN)0, : g(x0)0 g(x0)0 => g(x0)=0 => f(0)c=0 => f(0)=c
: f(x) , =f()={f():}
( - .)
: 1,2; 12, 1,2: 1=f(1), 2=f(2).
[1,2] ( 1<2)
[2,1] ( 2<1) , =f() => -
.
25. .
: () f g f(g(x)) - g -
g(x) - f.
: Lim g(x)=b ( xa) f - b, Lim f(g(x))=f(b) ( xa)
:
xN: xNa - - - f(g(x)), ,
yN: yN=g(xN) b . . Lim f(yN)=f(b)
(n) . - f . .. Lim f(g(xN))=Lim f(yN)=f(b) (n).

13
- yN - ( ) b.
yNb
f(yN)f(b)
: g x0, f 0=g(x0),
- f(g(x)) 0.
30. .
: f f()=
f().
: f .
0 f(0)=0 - f.
: ( ) - f
. f,
Y=f(), ( )
Y.
: f .
,
Y, 0
0, f(0)=0.
: 1> <0, f(1)> <f(0).
0 0 Y
: =f() - f. f`(y) f(x)
. y<y =f`(), =f`(), f` - f => =f() =f()
>, f > - , =,
= - .
f` : , Lim f`()=( 0) 0. f`(0)=0.
>0. : |f`()-f`(0)|< <=> 0-<f`()<0+ <=> f(0)<<f(0+) <=> f(0-)-0<-0<f(0+)-0 <=> -<-0<, =0-f(0-)>0-f(0)=0,
=f(0+)-0>f(0)-0=0,
=min{,} : |-0|< => -<-0< <=> |f`()-f`(0)|<
:
: Q M/N - mZ, nN.
- c
- M 1/M => - M/N - >0. =0, M/N = 1,
.
- N, nN:
=.
n=0: N => N - -N=1/N, :
1) 1/ - 0
2) N (nN) -
3) -N=1/N - - 1/ N 0
- : -N - 0, ..
MmZ - - 0. >0 - N nN
- N=> ,
( m>0), 1/N
( )
=> =>
-
31. .
: : X, >0,
1 xQ.
: mZ nN
1) (M)1/N = (1/N)M
(M)1/N=(((1/N)N)M)1/N = ((1/N)N*M)1/N = (((1/N)M)N)1/N = (1/N)M
2) (M)1/N=b <=> M=bN
3) (M*K)1/N*K=(M)1/N
(M*K)1/N*K=b <=> M*K=bN*K <=> M=bN <=> (M)1/N=b

14
- :
aM/N=(M)1/N=(1/N)M, a-M/N=1/aM/N, 0=1
-: x,yQ
1) aX * aY = aX+Y
aX * aY =b; x=m/n, y=-k/n => aM/N * 1/aK/N = b => aM/N = b * aK/N => aM = bN * aK => aM-K = bN => a(M-K)/N =
b => aX+Y = b
2) aX/aY = aX-Y
3) (aX)Y=aX*Y
(aX)Y=b; x=m/n, y=k/s => (aM/N)K/S=b => (aM/N)K=bS => (a1/N)M*K=bS => (aM*K)1/N=bS => aM*K=bS*N => a(M*K)/
(S*N)
=b => aX*Y=b
4) x<y => aX<aY (a>1) -
z=y-x>0; aY=aZ+X => aY-aX=aZ+X-aX=aX*aZ-aX=aX*(aZ-1) => aZ>1 z>0, aX<aY.
z=m/n => aZ=(a1/N)M => a1/N>1 => (a1/N)M>1 => aX*(aZ-1)>1, (a>1 n>0)
5) x0 aX1 (xR)
.. Lim a1/N=1 (n), , Lim a-1/N=Lim1/a1/N=1 (n). >0 n0: n>n0 1E<a-1/N<a1/N<1+E, >1. |x|<1/n0,
a-1/N<aX<a1/N => 1-E<aX<1+E. => Lim aX=1 ( x0)
32. .
: : X,
>0, 1 xR.
: x,yR.
1) aX * aY = aX+Y
xNx, yNy => aXn * aYn = aXn+Yn => Lim aXn * aYn = Lim aXn+Yn => Lim aXn * lim aYn = Lim aXn+Yn => aX *
aY = aX+Y
2) aX / aY = aX-Y
3) (aX)Y=aX*Y
xNx, yKy => (aXn)Yk = aXn*Yk => (n) (aX)Yk=aX*Yk =>(k) (aX)Y=aX*Y
4) x<y => aX<aY (a>1) - .
x<x x,xR; xNx xNx xN,xNQ => xN<xN => aXn < aXn => (n) aXaX-
x-x`>q>0 => aX-X aQ>1 => aX-X1 => aX<aX -
5) x n0 aX 1
.. Lim a1/N=1 (n), , Lim a-1/N=Lim1/a1/N=1 (n). >0 n0: n>n0 1E<a-1/N<a1/N<1+E, >1. |x|<1/n0,
a-1/N<aX<a1/N => 1-E<aX<1+E. => Lim aX=1 ( x0)
6) aX -
Lim aX=1 (n0) (5) - aX 0 => aX-aXo= aXo(aX-Xo - 1) x0
x-x0 n0 => aX-x0 n1 => x0 lim(aX - aXo)=
Lim aXo*Lim(aX-Xo - 1) = x0 * 0 = 0 => aX -
33. (1+x)1/X x 0 .
1) Lim (1+x)1/X = e x0
Lim (1+1/n)n = e n
: nK nKN (1+1/nK)Nke
:
E>0 k0: n>n0 0<e-(1+1/n)n<E => nK k0: k>k0 => nK>n0 => 0<e-(1+1/nk)Nk<E
Lim (1+xK)1/Xk x0+:
1/xK=zK+yK, zKN => 0yK<1 => (1+1/zK+1)Zk<(1+xK)1/Xk <
(1+1/zK)Zk+1=(1+1/zK)Zk*(1+1/zK)=>(1+1/zK+1)Zk=(1+1/zK+1)Zk+1)/(1+1/zK+1) => (1+1/zK+1)Zk+1/(1+1/zK+1) <
(1+xK)1/Xk < (1+1/zK)Zk*(1+1/zK) k , : (1+1/zK)1 (1+1/zK+1)1 => :
eLim (1+xK)1/Xke => Lim (1+xK)1/Xk=e => Lim (1+x)1/X=e x0+
Lim (1+xK)1/Xk x0-:
yK=-xK0+ => => Lim (1+x)1/X=e x0 => Lim (1+x)1/X=e x0
2) n lim (1+x/n)N = (lim (1+x/n)N/X)X = eX
3) xx R -

15
x=(eLn x) =e*Ln x

xLn x*Ln*Ln x => xe*Ln x


4) x0 Lim (Ln (1+x))/x = Lim Ln (1+x)1/X = Ln e = 1
4) x0 Lim LogA(1+x)1/X = 1/Ln a
5) x0 Lim (eX-1)/x = {eX-1=t} = Lim t/Ln(1+t) => (4) = 1/1 = 1
5) x0 Lim (aX-1)/x = Ln a
6) x0 Lim ((1+x)-1)/x = Lim ([e *Ln (1+x) -1]/[Ln(1+x)][Ln (1+x)]/x = 11=
34. .
f(x)
.
: [a,b], (1
) (2
).
: m=Sup{f(x):x[a,b]}. f [a,b], m=,
mR. - (N), Lim cN=m. .. nN: cN<m
xN[a,b]: cN<f(xN)m. xN - => xKn. .. axnb => [a,b].
mR - , - -
cKnm.
m=+ - - - - -
cKnm. - cKn<f(xKn)m,
Lim f(xKn)=b n, - f Lim f(xKn)=f() => f()=m -
f
. =Inf{f(x):x[a,b]} .
35. . .
: >0 >0: ,: |-|< => |f(x)-f(x)|< =>

, ,
.
: - f - , >0 >0: ,: |-|< => |f(x)f(x)|>0
{|f(x)-f(x)|:|x-x|<, x,xI}, IDf.
Wf() f
I :
1/ - Wf() = +; Sin x - Wf() = 1
: >0 >0:
Wf() Lim Wf()=0 0
36. .
: f [a,b], [a,b].
( ):
f [a,b]=>>0 >0 ,: |-|<=>|f(x)-f(x)|.
=1/, N K, K[a,b]: |K-K|<1/ |f(xK)-f(xK)|E
. K - => - - xKs
0. : |Ks-Ks|<1/
Ks-1/k<Ks<Ks-1/k - Ks0 kS |f(xKs)-f(xKs)|E S => 0E .
37. .
x0 xf(x): x0 -
. x0,
. .. / (x 0,f(x0) =>
( ) y=k*(x-x0)+f(x0). -
k . 0 , x0+.

16
, (x0,f(x0)), (x0+,f(x0+)). : =()(-x0)+f(x0),
k=f((x0+)-f(x0))/ - . Lim () 0,
k . Lim ()= 0,
x=(1/k())*(y-f(x0))+x0 0, x=x0 (Lim x=Lim
x0 0 => x = Lim x0)
: f 0 f(0)=Lim
(f(x0+)-f(x0))/ xx0, .
f(0) - (x 0,f(x0)).
y=f(x0)*(x-x0)+f(x0). Lim (f(x0+)-f(x0))/= 0, f`(x0)=
=x 0. f`(x0)=lim(f(x0+)-f(x0))/
xx0=>(f(x0+)-f(x0))/=f(x0)+(x), (x)0 xx0. f(x0+)-f(x0)=f`(x0)*+(x)*
, x0+=x (x)* o(x-x0) f(x)=f(x0)*(x-x0)+f(x0)+o(x-x0).
, o(x-x0) (x-x0) xx0 (.. o(x-x0)/(x-x0)0
xx0)
: - f x0 R:
x0 f(x)=(x-x0)+f(x0)+o(x-x0)
: x0 <=> f(x0)
:
<=: f(x)=f(x0)*(x-x0)+f(x0)+o(x-x0) => f`(x0)=C
=>: f(x)=C(x-x0)+f(x0)+o(x-x0) => (f(x)-f(x0))/(x-x0)=C+o(x-x0)/(x-x0)=C+(x), (x)0 xx0.
xx0 => Lim (f(x)-f(x0))/(x-x0)=C+0=C =>
- f => C=f`(x 0)
: f(x) x0,
f(x0)* f x0
df(x0). (- - dx). .. df(x0):f`(x0)* d:.
df(x0)=f(x0)*d => df(x0)/d: f`(x0)*/=f(x0) 0.
f(x0)=df(x0)/d - . -
.
: - f - x0, f x0.
: f(x)=f(x0)+f(x0)*(x-x0)+o(x-x0)f(x0) xx0 => f x0.
: - f x0: - f
x0. tg(90+ )=
-Ctg( ), : y=-1/f(x0)*(x-x0)+f(x0)
38. -. .
: - f g x0, - f+g, f*g f/g ( g(x0)0)
x0 :
1) (f+g)(x0)=f(x0)+g(x0)
2) (f*g)(x0)=f(x0)*g(x0)+f(x0)*g(x0)
3) (f/g)(x0)=(f(x0)*g(x0)-f(x0)*g(x0))/g(x0)2
:
1) f(x0)=f(x0+x)-f(x0)
g(x0)=g(x0+x)-g(x0)
(f+g)(x0)=f(x0)+g(x0)=f(x0+x)-f(x0)+g(x0+x)-g(x0)
(f+g)(x0)/x=(f(x0+x)-f(x0)+g(x0+x)-g(x0))/x=(f(x0+x)-f(x0))/x+(g(x0+x)g(x0))/xf(x0)+g(x0) x0
2) (f*g)(x0)=f(x0+x)*g(x0+x)-f(x0)*g(x0)=(f(x0)+f(x0))*(g(x0)+(x0))f(x0)*g(x0)=g(x0)*f(x0)+f(x0)*g(x0)+f(x0)*g(x0)
(f*g)(x0)/x=g(x0)*(f(x0)/x)+f(x0)*(g(x0)/x)+
(f(x0)/x)*(g(x0)/x)*xf(x0)*g(x0)+f(x0)*g(x0) x0
3) - g - x0 => - g - x0 => >0 (=|g(x0)|/2)
>0: |x|< => |g(x0+x)-g(x0)|<|g(x0)|/2.
g(x0)-|g(x0)|/2<g(x0+x)<g(x0)+|g(x0)|/2. g x (|x|<)
g(x0+x)0.

17
(1/g(x0+x)-1/g(x0))/ x = -(g(x0+x)-g(x0))/x*g(x0+x)*g(x0) -g(x0)/g(x0)2
x0
(f/g)(x0)=(f*1/g)(x0) => (2) = f(x0)*1/g(x0)+f(x0)*(1/g)(x0)=f`(x0)*1/g(x0)+f(x0)*(g(x0)/g(x0)2)=(f(x0)*g(x0)-f(x0)*g(x0))/g(x0)2
: f=Sin(x), g=Cos(x)
1) Sin(x0) = Cos (x0)
2) Cos(x0) = -Sin (x0)
:
1) f/x=(Sin(x0+x)-Sin(x0))/x = Sin(x/2)/(x/2) * Cos(x0+x/2) os x0 x0
2) g/x=(Cos(x0+x)-cos(x0))/x=Sin(x/2)/(x/2)*-Sin(x0+x/2) -Sin x0 x0
Tg Ctg Sin Cos
.
39. . ,
.
: g - x0, - f - y0=g(x0), -
h()=f(g()) - x0 h(x0)=f`(y0)*g(x0)
:
y=y-y0, x=x-x0, f(y0)=f(y0)*y+o(y), g(xo)=g(xo)*x+o(x), y=g(x0+x)
h(x0)=f(g(x0+x))-f(g(x0))=f(y)-f(y0)=f(y0)*y+o(y)=f(y0)*(g(x0+x)-g(x0))
+o(g)==f(y0)*(g(x0)*x+o(x))+o(y)= f(y0)*g(x0)*x+f(y0)*o(x)+o(y)
h(x0)/x=f(y0)*g(x0)+r, r=f`(y0)*o(x)/x+o(y)/x
r=f`(y0)*o(x)/x+o(y)/x=f`(y0)*((x)*x)/x+((x)*y)/x=f(y0)*(x)+(x)*y/xf(y0)*0 +
0*g(y0) x0 ((x)0 (x)0)
:
1) x=*x-1
Lim (y/x)=lim((x+x)-x)/x = Lim x1* ((1+x/x)1)/x/x.
x0 Lim ((1+x)-1)/x=, x0
Lim x1*Lim((1+x/x)1)/x/x = x1
2) (aX)=aX*Ln a (xaX)=(xeX*Ln a)
xeX*Ln a - xX xx*Ln a R => (xaX)=(x X*Ln
a)=(xX*Ln a)*(xx*Ln a)=aX*Ln a
- : (eX)=eX
Lim(y/x)=Lim(eX+X-eX)/x=LimeX*(eX-1)/x, - x0 Lim(eX-1)/x=1,
x0 Lim(y/x)=eX
3) (LogA(x))=1/x*Ln a
Lim(y/x) = Lim (LogA(x+x) - LogA(x))/x = Lim 1/x*LogA(1+x/x)/x/x,
x0 Lim LogA(1+x)/x=1/Ln a,
Lim (y/x) = Lim 1/x*Lim LogA(1+x/x)/x/x=1/x*Ln a
40. . .
: g - f y0,
g(y0)=1/f(x0), y0=f(x0)
: g(f(x))=x g(f(x))=1
g(f(x0))=g(f(x0))*f(x0)=1, g(f(x0))=g(y0)=1/f(x0)
: - f (,) (,b)
- g, (,b) (,). f -
x0(,) f(x0)0, g - y0=f(x0) g(y0)=1/f(x0)
:
y0: yNy0, yNy0 => - xN:
xN=g(yN), f(xN)=yN
g(yN)-g(y0)/yN-yO = xN-xO/f(yN)-f(yO) = 1/f(yN)-f(yO)/xN-xO 1/f(xo) n, xNxO
g(yN)-g(yO)/yN-yO1/f(xO) => g(O)=1/f(xO)
:

18
1) xrcsin x Arcsinx=1/Siny, Sin y=x , Siny<0,
( ): Arcsinx=1/Cos y, .. rcsin: [-1,1][-/2,/2] Cos:[/2,/2][0,1], Cos y0 , Arcsinx = 1/Cos y = 1/(1-Sin2y)1/2 = 1/(1-x2)1/2
2) xArccosx = -1/(1-x2)1/2
3) xArctgx = 1/1+x2
4) xArcctgx= -1/1+x2
41. .
: - f - xO, - f(x):xf(x)
- xO .
- f(x) - ( 2) - f
xO f(x).
. fN(xO) - n f xO
n=0 f0(xO)=f(xO).
: C n
(n-1) xO ( -
), xfN-1(x) xO, n2
(n-2) xO.
: - f n xO dfN(x)*d
dNf(x). dNf(x):dfN(x)dxN.
fN(x)dN:dfN(x)dxN, dNf(x)=fN(x)dN. fN(x)
dNf(x)/dN
:
=f() =g(t) , =f(g(t)).
() (t) c (t)=()*(t).
, - dy=y()dx. t,
(t)=()*(t): dy=y(t)dt=y(x)*(t)dt. x(t)dt=d =>
dy=y(t)dt=()*(t)*dt=(x)d -
-
.
=f() =g(t) , =f(g(t))
() (t) (t)=()*(t)
- t dy=y()d, d=x(t)dt.
- t: d2y=d(y(x)dx)=dy(x)dx+y(x)d(dx).
- dy(x)=( 2)dx => d2y=( 2)dx2x+y(x)*d2x,
- 2y=( 2)*dx2x => -.
:
n

f(x)=u(x)*v(x)

f n (x) =

k
n-k
Ck
(x)
n * u (x) * v

k =0

.
1) n=0
2) n - => (n+1)
u v (n+1) , - :
n

f n+1 = (

k=0

C kn * (u k (x) * v n-k x))' =

k=0

C kn * (u k+1 (x) * v n-k (x)) +

C kn * (u k (x) * v n+1-k (x))

k=0

,
u v ( ,
, (n+1)). u0*vN+1
0N=1. uN+1*v0
NN=1. uK*vN+1-K.
k = i-1, i=k. .
Cnk+1 = Cnk + Cnk 1 =>
42. .
.
: I=(a;b), x0(a;b). x0,
min(max), x(a;b),

19
f(x0)<f(x) (f(x0)>f(x)).
: f(x) x0.
f(x0)>0(f(x0)<0), , x0 , f(x)>f(x0) (f(x)<f(x0)),
x, , f(x)<f(x 0) (f(x)>f(x0)).
f ( x) f ( x 0 )
: , f ' ( x 0 ) = Lim
.
x x0
x x0
f(x0)>0, (x0-,x0+) x0, ( x0) (f(x)-f(x0))/
(x-x0)>0. x0<x<x+, -0>0 => , f(x)-f(x0)>0,
.. f(x)>f(x0). x-<x<x0 -0<0, f(x)-f(x0)<0, .. f(x)<f(x0). ...
: f(x) I=(a;b)
x0 () . f(x)
x0, f(x0)=0.
: f(x) x 0.
, f(x0)0, : f(x0)>0, ( )
f(x)>f(x0), x>x0 x0, f(x0)<0, f(x)>f(x0), x<x0
x0. f(x0) f(x)
I=(a;b) => => .
: () [a;b]
, , ,
.
43. , , ( ).

1) f(x) [a;b]
2) f(x), (a;b)
3) : f(a)=f(b)
a b c(a<c<b), f()=0.
: f(x) [a;b] ,
( f(x), [a;b],
),
M, m.
:
1) M=m. f(x) [a;b] : mf(x)M
x f(x)=M => f(x)=0 ,
(a;b).
2) M>m. , ,
f(a)=f(b), a b.
( f(x) I=(a;b)
x0 () . f(x)
x0, f(x0)=0) , f()
.
:
1) f(x) g(x) [a;b] & g(b)g(a)
2) f(x) g(x),
(a;b)
3) g(x)0 (a;b)
a b c(a<c<b),

f (b) f ( a )
f ' ( c)
=
g (b) g ( a )
g ' ( c)

: h(x)=[f(x) - f(a) -

f (b) f ( a )
g (b) g (a )

:
1) h(x) [a;b],
2) h(x) (a;b), h(x)=f(x) -

*(g(x) - g(a))]

f (b) f ( a )
g (b) g (a )

*g(x)

3) h(a)=h(b)=0
(a;b) , h(x)=0 => f(c) *g(c) f(c) =

f (b) f ( a )
g (b) g (a )

*g(c).

g(x) (g(x)0) .

f (b ) f ( a )
g (b ) g ( a )

20
:
1) f(x) [a;b]
2) f(x), (a;b)
f (b) f ( a )
= f ' ( c)
a b c(a<c<b),
b a
: , g(x)=x, :

f (b ) f ( a )
= f ' ( c)
b a

=+(b-a), (0;1).
x0=a, (b-a)=h, :
: f(x) I=(a;b), x0, x0+h,
(0;1): f(x0+h)-f(x0)=f(x0+h)*h ([x0;x0+h] h>0, [x0+h;x0] h<0)
n+1

N+1

(x)=u *v

N+1

k
n+1-k
Ck
(x)
n+1 * u (x) * v

k=0

n+1

+u

N+1

*v =

k
n+1-k
Ck
(x)
n+1 * u (x) * v

k=0

44. .
: f(x) [a;b] -
(a;b), f(x)=0 (a;b), f(x)-const [a;b].
:
xb, [a;x] : f(x)-f(a)=f(a+(x-a))
(x-a) 0<<1 => .. f(x)=0 (a;b), f(a+(x-a))=0 => f(x)=f(a)=Const (a;b).
: f(x) [a;b] -
(a;b), :
1) f () (a;b) <=> f(x)0(f(x)0) (a;b).
2) f(x)>0(f(x)<0) (a;b) f [a;b], f () [a;b].
:
1) f [x,x] x, x(a;b), (f(x)-f(x))/(x-x)=f(c),
(x,x). f(x)0(f(x) 0) (a;b) => f(c)0(f(c) 0) => f(x)f(x)( f(x)f(x))
=> f(x) () (a;b).
2) (1) , (2).
: xO- - f. f(x) --
xO , xO- .
: (+)xO(-) => min, (-)xO(+) => max
46. Rn. . . .
: <=> , [,]
[,] => [,]={+t(-):t[0,1]} => (1-t)+t
[,] => ,; 1=1-t, 2=t => 1+2=1 1,20 => 1+2
: 1,2,...N 1,20 (i=1,n): = 1
(i=1,n): *I
-: :
1) n=1, n=2 -
2) (n-1) - => n:
) =1 => 1=...= 1=0 =>
) <1 1*1 +...+ 1* 1 + * = (1- )((1/1- )*1+...+(1/1- )* 1) + * = (1 )*B + *
B - - =>(1- )*B + * ..
f = {(x,f(x)):Df}, UPf={(x,y):y>f(x)}
: f <=> UPf - .
: I 0 (i=1,n): =1 => (i=1,n): *I , xI0, f(xI)yI => (i=1,n): *I
= (xI;*yI) => f(xI)*yI
: I 0 =1f(xI)*f(xI)
47. .
: f (a;b), : 1) f (a;b) ~ 2) x,xO,x(a;b) x<xO<x =>
(f(xO)-f(x))/(xO-x)(f(x)-f(xO))/(x-xO). :
.

21
:
=> AB: k=(y-f(x))/(xO-x)(f(xO)-f(x))/(xO-x) => yf(xO); AB: k=(f(x)-y)/(x-xO)(f(x)-f(xO))/(xxO) =>yf(xO)
(f(xO)-f(x))/(xO-x)(f(x)-f(xO))/(x-xO)
<=